Kiai dan Lingkungan Hidup; Revitalisasi Krisis Ekologis Berbasis Nilai Keagamaan di Indonesia - Muhammad Afwan Romdloni; Muhammad Sukron Djazilan (Universitas Nahdlatul Ulama Surabaya, 2019)
The environment becomes an important part of human life, without which humans would not be able to survive in the world. However, with the greedy nature and economic libido makes people forget and neglect the risks that will be experienced. This happens because human awareness of their responsibilities as kholifah in charge of balancing the condition of the earth has vanished. This ecological awareness comes from the beliefs of every individual. So that the function of religion is expected to be a role of view in human life in order to preserve the environment as a form of ijtihad for the earth. The more so it can integrate the teachings of monotheism, and Sufism should be compounded with the teachings of fiqh so that the concept of an holistic-integral environment appears. In this case a religious leader has a very important role as an agent of change, as well as being able to provide confidence, motivation and solutions in restoring the ecological crisis that has plagued Indonesia and even the world. Although not all kiai have the same role, at least they have a breath of fresh air in an environmental problem with a religious perspective.